1997
DOI: 10.1152/jappl.1997.82.6.1776
|View full text |Cite
|
Sign up to set email alerts
|

Selective endothelial dysfunction in conscious dogs after cardiopulmonary bypass

Abstract: It has previously been demonstrated that cardiopulmonary bypass (CPB) causes prolonged pulmonary vascular hyperreactivity (D.P. Nyhan, J.M. Redmond, A.M. Gillinov, K. Nishiwaki, and P.A. Murray. J. Appl. Physiol. 77: 1584-1590, 1994). This study investigated the effects of CPB on endothelium-dependent (acetylcholine and bradykinin) and endothelium-independent (sodium nitroprusside) pulmonary vasodilation in conscious dogs. Continuous left pulmonary vascular pressure-flow (LP-Q) plots were generated in consciou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Brachial artery FMD measures vasodilation following an acute increase in blood flow (reactive hyperemia), typically induced by a period of circulatory occlusion [4]. It has been suggested that major surgery–and in particular, the use of cardiopulmonary bypass surgery (CBS)–triggers a systemic inflammatory response, resulting in endothelial dysfunction [511].…”
Section: Introductionmentioning
confidence: 99%
“…Brachial artery FMD measures vasodilation following an acute increase in blood flow (reactive hyperemia), typically induced by a period of circulatory occlusion [4]. It has been suggested that major surgery–and in particular, the use of cardiopulmonary bypass surgery (CBS)–triggers a systemic inflammatory response, resulting in endothelial dysfunction [511].…”
Section: Introductionmentioning
confidence: 99%
“…21 ACh-related NO pathway appears to be preferentially damaged. 10,22 Indeed, Gagnon and colleagues 10 have shown in a porcine model that CPB with reperfusion of the pulmonary tree induces a decrease in endotheliumdependent relaxation mediated by muscarinic receptors, which was also demonstrated in a dog model by Zanaboni and colleagues. 22 Although ACh induces endothelium-dependent relaxation through both the NO and cAMP pathways, 23 more specific signal transduction pathways alterations may explain the lack of benefit of inhaled PGI 2 in ACh-induced dysfunction in this study.…”
Section: Discussionmentioning
confidence: 86%